Stenus „aterrimus“ - ein Komplex aus sechs wirtsspezifischen myrmecophilen Arten (Coleoptera: Staphylinidae; Hymenoptera: Formicidae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2009)
Stenus aterrimus Erichson, 1839, absolutely myrmecophilous and associated with Formica species, appeared as a complex from six species, five of them absolutely host specific to a single Formica species each. For the sixth this is unknown, but to hypothetisize. The examination of the lectotype appeared that S. aterrimus is the species which is connected with Formica truncorum Fabricius, 1804. The following five species are described as new: Stenus polyctenicola sp. n. (locus typicus: Germany, Mecklenburg-Vorpommern, Altwarp; host ant Formica polyctena Förster, 1850), Stenus ruficola sp. n. (type locality: Germany, Brandenburg, Forst Bredow near Brieselang; host ant: Formica rufa Linnaeus, 1758), Stenus pratensicola sp. n. (type locality: Germany, Brandenburg, Eberswalde; host ant: Formica pratensis Retzius, 1783), Stenus spielfeldensis sp. n. (type locality: Austria, Steiermark, Spielfeld-Strass in Steiermark; host ant: most likely Formica sanguinea Latreille, 1798), and Stenus sarajevensis sp. n. (type locality: Bosnia and Hercegovina, Sarajevo; host ant unknown). Keywords Staphylinidae, Stenus, taxonomy, new species, Germany, Austria, Bosnia and Hercegovina, myrmecophily, host specifity, host ants, Formicidae, Formica. Nomenclatural Acts polyctenicola Zerche, 2009 (Stenus), spec. n. pratensicola Zerche, 2009 (Stenus), spec. n. ruficola Zerche, 2009 (Stenus), spec. n. sarajevensis Zerche, 2009 (Stenus), spec. n. spielfeldensis Zerche, 2009 (Stenus), spec. n.